The Ceja family - Manuel Echavarria::::::photographer:::
The Ceja family, Santa Maria residents and ardent UFW advocates take their case to the steps of the State Capital, Sacramento, to lobby in favor of farm worker rights. It was commonplace for local supporters to travel to various parts of California and the nation, to advocate on behalf on the Union. La familia Ceja, residentes de Santa Maria y fervientes simpatizantes de la UFW llevaron su caso hasta la capital del estado, Sacramento, para intensificar el apoyo en favor de los derechos de los trabajadores agrícolas.